2018
DOI: 10.1016/j.jalgebra.2017.12.032
|View full text |Cite
|
Sign up to set email alerts
|

Identities in upper triangular tropical matrix semigroups and the bicyclic monoid

Abstract: We establish necessary and sufficient conditions for a semigroup identity to hold in the monoid of n × n upper triangular tropical matrices, in terms of equivalence of certain tropical polynomials. This leads to an algorithm for checking whether such an identity holds, in time polynomial in the length of the identity and size of the alphabet. It also allows us to answer a question of Izhakian and Margolis, by showing that the identities which hold in the monoid of 2×2 upper triangular tropical matrices are exa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
51
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(51 citation statements)
references
References 34 publications
0
51
0
Order By: Relevance
“…If, however, an infinite semigroup satisfies a nontrivial identity, its identity checking problem may constitute a challenge: Murskiǐ [1968] had constructed an infinite semigroup with undecidable identity checking problem. On the 'positive' side, we mention a recent result by Daviaud et al [2018] who have shown that checking identities in the famous bicyclic monoid B := a, b | ba = 1 can be done in polynomial time via rather a non-trivial algorithm based on linear programming.…”
Section: Recognizing Identities Of K 3 In Polynomial Timementioning
confidence: 99%
“…If, however, an infinite semigroup satisfies a nontrivial identity, its identity checking problem may constitute a challenge: Murskiǐ [1968] had constructed an infinite semigroup with undecidable identity checking problem. On the 'positive' side, we mention a recent result by Daviaud et al [2018] who have shown that checking identities in the famous bicyclic monoid B := a, b | ba = 1 can be done in polynomial time via rather a non-trivial algorithm based on linear programming.…”
Section: Recognizing Identities Of K 3 In Polynomial Timementioning
confidence: 99%
“…Both of these operations are costly when the words are long. Our approach is based upon a geometric interpretation of the characterisation of UT n (T) identities given in [6], which involves more polynomial pairs but in fewer variables and monomials. A key observation is that the polynomials which appear in [6] are tropical polynomials with trivial coefficients, and thus they are equal if and only if their Newton polytopes are equal.…”
Section: Introductionmentioning
confidence: 99%
“…Our approach is based upon a geometric interpretation of the characterisation of UT n (T) identities given in [6], which involves more polynomial pairs but in fewer variables and monomials. A key observation is that the polynomials which appear in [6] are tropical polynomials with trivial coefficients, and thus they are equal if and only if their Newton polytopes are equal. This translates the problem to verifying equality of lattice polytopes, which can be efficiently computed and, more importantly, adds geometric insights that allow us to deduce structural information about these identities.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations